Data Management in Grid and Peer-to-Peer Systems Second International Conference, Globe 2009 Linz, Austria, September 1-2, 2009 Proceedings - Hameurlain, Abdelkader.; Tjoa, A Min. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the Second International Conference on Data Management in Grid and P2P Systems, Globe 2009, held in Linz, Austria, in September 2009. The 9 revised full papers presented were carefully reviewed and selected from 18 submissions. The papers are organized in topical sections on grid systems, querying in P2P systems, privacy protection for P2P systems, and semantic for P2P systems and applications.